Agreement of Peru-Based Allergy Tests for Respiratory Allergens in Allergic Rhinitis Patients - César Galván; Margarita Totesaut; Edgar Muñoz; Rafael Durán; Christian La Rosa; Oscar Calderón (Journal of Immunology Research)
Background. The Peruvian Immunoblot panel, together with traditional skin prick tests (SPT), are widely used in vitro allergy tests in Peru. In addition to this, Peruvian allergists are increasingly adopting multiplex tests such as the ALEX-2 (Macro Array Diagnostics). Previous studies have revealed limited agreement between Immunoblot and SPT results. Therefore, our study aimed to evaluate the concordance between these three tests in patients with allergic rhinitis (AR) in a private center in Arequipa, Peru. Materials and Methods. We enrolled 35 patients, including children over 3 years and adults, with AR. Clinical and demographic data were collected, and patients underwent allergic sensitization testing using the Immunoblot Peruvian panel (32 allergens), ALEX-2 (295 allergens), and SPT (12 allergens). Concordance was calculated using Cohen’s kappa coefficient and analyzed with IBM SPSS V26. Results. Among the patients, 34.3% exhibited moderate-to-severe persistent AR, and 14.3% had asthma. Additionally, 85.7% reported a family history of AR. Sensitization rates varied notably between the SPT and ALEX-2, particularly for olive pollen (34.3% vs. 17.4%), Blomia tropicalis (11.4% vs. 17.1%), and grasses (11.4% vs. 28.5%). Remarkably, these allergens were not included in the Peruvian Immunoblot panel. Concordance analysis included seven allergens and showed significant concordance between ALEX-2 and SPT for five allergens, between Immunoblot and SPT for two allergens, and between ALEX-2 and Immunoblot for two allergens. Conclusion. This preliminary study shows us a better concordance between ALEX-2 and SPT rather than between Immunoblot and SPT.